MANAJEMEN INOVASI KEPALA SEKOLAH DI ERA INDUSTRI 4.0: OPTIMALISASI TEKNOLOGI DALAM PEMBELAJARAN TK NEGERI PEMBINA BATUMANDI - Chairunnisa; Khuzaini; Syahrial Shaddiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The Industry 4.0 era mandates that school principals manage innovation to optimize learning technology. This study aims to analyze (1) the principal's innovation management strategies, and (2) the enabling and inhibiting factors for technology optimization at TK Negeri Pembina Batumandi. The research utilizes a qualitative approach with a case study design. Data were collected through in-depth interviews with teachers (IG) and school operators (IO), observations, and documentation studies. Data were analyzed thematically. The findings indicate the principal implements a dual strategy: (a) a managerial strategy, focusing on prioritizing the ICT budget and asset management systems (per IO findings), and (b) a transformational/cultural strategy, creating a psychologically safe climate for innovation and employing dialogical supervision (per IG findings). The primary enabling factor is the principal's "tech-savvy" and adaptive leadership. Inhibiting factors were identified at two levels: internal (operational efficiency of device setup and maintenance management) and external (unstable internet and electricity infrastructure). The study concludes that the principal's innovation management successfully combines systemic (budgetary) and cultural (psychological) support, yet its effectiveness remains constrained by external infrastructural challenges.